Development of Seribu Rumah Gadang Village as a Tourism Destination - Putra, Gisky Andria (Yayasan Maslahatul Ummah Ilal Jannah, 2024)
The Seribu Rumah Gadang village is one of the potential tourist destinations to be developed. The aim is to ensure that the tourism sector in West Sumatra continues to progress and grow, thereby increasing the economic sector. This research is a descriptive study with a qualitative approach. The data analysis technique used is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The study results indicate that the strategy for developing the village of a thousand